2017
DOI: 10.1021/acssuschemeng.7b02074
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and Selective Lipid Extraction from the Microalga P. tricornutum by Dimethyl Carbonate and Supercritical CO2 Using Deep Eutectic Solvents and Microwaves as Pretreatment

Abstract: Microalgae are a promising alternative source of several bioactive compounds useful for human applications. However, lipids are traditionally extracted with toxic organic solvents (e.g. mixture of chloroform and methanol or hexane). In this work, we developed a new lipid extraction protocol to obtain a fatty acids rich extract from the diatom Phaeodactylum tricornutum. Deep Eutectic Solvents (DES) and microwaves (MW) were investigated as pre-treatments for environmentally friendly solvent extractions using dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…were recovered by the B&D-based method, but not the Lewis's method, that recovered much less. Tommasi et al [28] reported a similar result, where the B&D method recovered most of the fatty acids from Phaeodactylum tricornutum. In contrast, Cavonius et al [29] reported that the Lewis's method showed higher fatty acid recovery from Nannochloropsis oculata and Isochrysis galbana, than B&D's method.…”
Section: Comparison Of Fame Extraction Methods For Biodiesel Productionmentioning
confidence: 72%
“…were recovered by the B&D-based method, but not the Lewis's method, that recovered much less. Tommasi et al [28] reported a similar result, where the B&D method recovered most of the fatty acids from Phaeodactylum tricornutum. In contrast, Cavonius et al [29] reported that the Lewis's method showed higher fatty acid recovery from Nannochloropsis oculata and Isochrysis galbana, than B&D's method.…”
Section: Comparison Of Fame Extraction Methods For Biodiesel Productionmentioning
confidence: 72%
“…Later, EtAc started replacing chloroform as an extraction solvent (Koster et al, 1994;Siebenhaller et al, 2016). More recently, to extract polar and nonpolar lipids from microalgae, DMC is used as an alternative to traditional chloroform extraction (Lee et al, 2013;Tommasi et al, 2017). On this account, these three solvents have been chosen to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…All of the NADESs were prepared based on the molar ratio of choline chloride and the hydrogen bond donor (HBD) and all ratios were presented in Section 3.1. The appropriate ratio for the preparation was taken from the literature [14,15]. Choline chloride (ChCl) and an HBD (of choice) were mixed at a specific molar ratio, and heated and stirred at a speed of 350 rpm and a temperature at 80 • C (Thermo Scientific TM , Waltham, MA, USA) for 2 h until a homogeneous and stable mixture with no visible precipitate was obtained.…”
Section: Nadess Preparationmentioning
confidence: 99%